CNS Activity of the Methanol Extracts of Sapindus emarginatus Vahl in Experimental Animal Models (Journal of Scientific Research, 2009)
The aim of the present study is to investigate central nervous system (CNS) activity of the methanol extract of Pericarp of Sapindus emarginatus (Sapindaceae) in Swiss albino mice and Wistar albino rats. A daily dose of 100 and 200 mg/kg of the extract was administered to the animals for 15 days, after which various CNS experiments were recorded and compared with the control animals. General behavior, exploratory behavior, muscle relaxant activity cocaine induced hyperactivity and phenobarbitone sodium-induced sleeping time were studied. The results revealed that the methanol  extract  of  Pericarp of Sapindus emarginatus at 100 and 200  mg/kg  caused  a  significant  reduction  in  the  spontaneous activity (general behavioral profile), remarkable decrease in exploratory behavioral  pattern (Y-maze  and  head  dip  test), a reduction in muscle relaxant activity (rotarod and traction tests), inhibition of cocaine induced hyperactivity and also significantly potentiated phenobarbitone sodium–induced sleeping time. The results suggest that methanol extract of Sapindus emarginatus exhibit CNS depressant activity in tested animal models. Keywords: Sapindus emarginatus; Cocaine; CNS activity; Experimental animals. © 2009 JSR Publications. ISSN: 2070-0237(Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.1772      J. Sci. Res. 1 (3), 583-593 (2009)